An Analysis Of Pastors' Failures In Evangelism And Their Impact On Congregational Growth - Yulian Anouw; Frediel Pigai; Sepenior Anouw (STT Transformasi Indonesia Manado, 2026)
Evangelization is the church's primary mandate in carrying out Christ's Great Commission, which plays a crucial role in the spiritual and quantitative growth of the congregation. Pastors, as spiritual leaders, have a strategic responsibility to mobilize evangelism, both directly and through congregational empowerment. However, in practice, many churches experience stagnation or a decline in membership due to the pastor's failure to carry out his evangelism function. This study aims to analyze the factors causing this failure and evaluate its impact on congregational growth. Using a qualitative approach through case studies in several churches in the Kingmi Classis Sorong Fakfak church area over the past 10 years, it was found that pastoral failure is influenced by a lack of missionary training, excessive administrative focus, and minimal social involvement. The consequences include a decline in the number of new members, a weakening spirit of service, and a reduced relevance of the church in society. This study recommends a renewal of spiritual leadership strategies that are more missionary and contextual to encourage sustainable congregational growth.